2021
DOI: 10.3389/fonc.2021.720620
|View full text |Cite
|
Sign up to set email alerts
|

Angelica Polysaccharide Antagonizes 5-FU-Induced Oxidative Stress Injury to Reduce Apoptosis in the Liver Through Nrf2 Pathway

Abstract: Oxidative stress induced by chemotherapeutic agents causes hepatotoxicity. 5-Fluorouracil (5-FU) has been found to have a variety of side effects, but its toxic effect on the liver and the mechanism are still unclear. Angelica polysaccharide (ASP), the main active ingredient of Dang Gui, has antioxidative stress effects. In this study, we investigated the antagonistic effects of ASP on 5-FU-induced injury in the mouse liver and human normal liver cell line MIHA and the possible mechanism. Our results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 82 publications
3
19
0
Order By: Relevance
“…5-FU-induced organ toxicity is accompanied by a marked reduction in Nrf-2 along with an increase in Keap-1. Hence, studies showed that activation of Nrf-2 could be beneficial in the protection against 5-FU-induced organ injury [35,36]. Similarly, data in the present study indicated that 5-FU induced a significant decrease in renal tissue expression of Nrf-2 protein compared to both normal and AuNPs control groups.…”
Section: Aunps Treatment Corrected 5-fu-induced Imbalance Of Nrf-2/keap-1 Axis In Renal Tissuessupporting
confidence: 78%
“…5-FU-induced organ toxicity is accompanied by a marked reduction in Nrf-2 along with an increase in Keap-1. Hence, studies showed that activation of Nrf-2 could be beneficial in the protection against 5-FU-induced organ injury [35,36]. Similarly, data in the present study indicated that 5-FU induced a significant decrease in renal tissue expression of Nrf-2 protein compared to both normal and AuNPs control groups.…”
Section: Aunps Treatment Corrected 5-fu-induced Imbalance Of Nrf-2/keap-1 Axis In Renal Tissuessupporting
confidence: 78%
“…Most drugs or their metabolites associated with liver damage cause hepatotoxicity by interfering with cellular antioxidant systems, causing free radical formation and oxidative stress [ 74 ]. Hepatotoxicity with 5-fluorouracil is also a well-known phenomenon [ 75 , 76 ]. This damage may be caused by the inhibition of thymidylate synthase.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding 5-fluorouracil, this chemotherapeutic agent has been shown to give toxicity, mainly increasing the expression of Keap1 and decreasing Nrf2 transcriptional activity, as well as to the inhibition of HO-1 and the aggravation of DNA damage [ 169 ].…”
Section: Nrf2 Pathway Modulation and Its Connection With Cardiotoxici...mentioning
confidence: 99%